Dinamika Penurunan Kunjungan Wisatawan Mancanegara di Bali Tahun 2025 - Inka Sulistya; Nova Aprilina (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
The decline in foreign tourist arrivals in Bali in 2025 represents a critical issue, given ‎the strategic role of tourism in regional economic development and community welfare. This ‎phenomenon occurs amid intensified global tourism competition and significant changes in ‎international travel behavior. This study aims to examine the dynamics of declining foreign ‎tourist arrivals in Bali and to identify the key factors influencing this trend. A descriptive ‎qualitative approach was employed by analyzing tourism-related conditions and phenomena ‎without relying on interview-based data. The findings indicate that the decline in foreign tourist ‎arrivals is driven by an interplay of global and local factors, including global economic ‎uncertainty, shifts in tourist preferences, destination overcrowding, environmental concerns, and ‎the perceived quality of tourism experiences. The impact of this decline extends beyond the core ‎tourism sector to supporting industries and local communities that depend on tourism-related ‎activities. These findings emphasize the need for adaptive and sustainable tourism management ‎strategies to strengthen Bali’s competitiveness as an international tourism destination amid ‎evolving global tourism dynamics.‎